The Role Of Explicit Pragmatic Instruction To Improve Second Language Learners' Ideational Metafunction Of The Target Language - hapsari, Astri (Journal of English and Education (JEE), 2013)
Pragmatics is considered to be the component of language which is hard to teach for beginner learners of English. Highlighting the argument on the model of language competence proposed by Bachman's (1990), this paper discusses how the definition of pragmatic competence in the field of TESOL should include illocutionary competence in Bachman's model. Taking the stance on functional grammar's perspective, a brief analysis is presented how explicit pragmatic instruction can improve second language learner's ideational metafunction of the target language.Keywords: explicit pragmatic instruction, ideational metafunction, functional grammar